Targeting DNA damage response deficiency in the treatment of breast cancer - JIN Yizi, LIN Mingxi, ZHANG Jian (Zhongguo aizheng zazhi, 2022)
DNA damage response (DDR) deficiency has been one of the emerging targets in treating breast cancer in recent years. The DDR pathway is essential for the identification, signal transduction and repair of DNA damage. Its dysfunction may lead to cell apoptosis or genomic instability. Poly (ADP-ribose) polymerase (PARP) inhibitors, ATM inhibitors, CHEK1 inhibitors, ATR inhibitors and WEE1 inhibitors are DDR drugs that already in the clinical development for treating breast cancer. In this review, we introduced the concept of DDR deficiency, the rationale and research advances in DDR-targeted drugs, and discussed the challenges in its clinical applications.